Bases experimentais para o projeto, automação e instalação de sistemas de geração de energia com células de combustível - Gonzatti, Frank (2005)
The main concern of this dissertation is the establishment of experimental bases for the project, automation, and installation of a micro-power plant for electric power generation based on PEM fuel cell stacks (BCS Technology). The plant operates automatically, and its control is accomplished by a microcontroller acting directly in the temperature, in the humidity of the membrane, in the amount of reaction air, in the monitoring of the individual voltage of each cell and in the attempt of recovery of a possibly problematic cell. For control operation special auxiliary mechanisms are necessary to avoid dangerous conditions to the stack. The making of the prototype is of low cost and easily found items in national market access have been intended. Special controlled atmospheres were also designed and built to shelter the stack and obtain safety operation when the stack is on. Therefore, the work tries to find the theoretical and experimental bases for a static power plant implementation based on fuel cell systems.